Pengaruh Manajemen Sarana dan Prasarana Pendidikan Terhadap Efektivitas Proses Belajar Mengajar di SMA 2 Mutiara - Darmi; Safia Maulida; Syahrul (Indonesia Economic Journal, 2025)
This study aims to determine the effect of educational facility and infrastructure management on the effectiveness of teaching and learning at Mutiara 2 High School. The research methodology used was a survey, using a questionnaire. The sample consisted of 28 teachers at Mutiara 2 High School. Data analysis used SPSS version 22 for validity and reliability testing. Normality and linearity tests were conducted, including hypothesis testing comparing the 5% probability value and hypothesis testing comparing the calculated t-value with the t-table. A simple linear regression test was then conducted to determine the solution. The results of this study indicate that educational facility and infrastructure management has a significant effect on the effectiveness of the teaching and learning process at Mutiara 2 High School, with a value of 0.001 <0.05 probability value. The determination test showed an R-square value of 0.0363. This value indicates that the influence of educational facility and infrastructure management (X) on the effectiveness of the teaching and learning process (Y) is 36.3%, while the remaining 63.7% can be influenced by other variables not examined.